A multistate mark–recapture approach to estimating survival of PIT‐tagged salamanders following timber harvest. Issue 5 (8th July 2015) - Connette, Grant M.; Semlitsch, Raymond D.
Summary: Survival is a critical component of individual fitness, population dynamics and the landscape ecology of organisms. Survival in animal populations is frequently estimated from capture–mark–recapture studies, yet these estimates are biased low when the permanent emigration of individuals is confounded with mortality. This systematic bias can limit the value of demographic information available for conservation and management efforts. We developed a novel multistate mark–recapture model for survival estimation in fossorial organisms that incorporates auxiliary passive integrated transponder (PIT‐tag) detection data to account for the possibility of permanent emigration from our study area as well as the imperfect detection of individuals. Our study provides a direct comparison of mortality, emigration and reduced ground surface activity as explanations for declines in terrestrial salamander counts which are commonly reported following timber harvest. Reduced ground surface activity was not supported as a likely cause for reduced counts of plethodontid salamanders after timber harvest. Instead, ground surface activity was predicted to be considerably higher after timber harvest, suggesting that surface counts would under‐represent the extent of population losses relative to control areas. Controlling for multiple causes for non‐detection of salamanders, we found evidence that survival probability was reduced while permanent emigration rates may also be elevated in the initial months after timber harvest. However, a substantial majority of salamanders were known to survive the process of initial forest stand entry and timber removal. Synthesis and applications . Our analysis of passive integrated transponder (PIT‐tag) detection data with a novel multistate mark–recapture model indicated that mortality and emigration are both potential causes for short‐term reductions in salamander abundance following timber harvest. We suggest that salamander mortality is likely tied to habitat or microclimate conditions in early successional timber cuts, rather than the physical process of timber removal. Abstract : Our analysis of passive integrated transponder (PIT‐tag) detection data with a novel multistate mark–recapture model indicated that mortality and emigration are both potential causes for short‐term reductions in salamander abundance following timber harvest. We suggest that salamander mortality is likely tied to habitat or microclimate conditions in early successional timber cuts, rather than the physical process of timber removal.